Stephen Turton. Before the Word was Queer: Sexuality and the English Dictionary, 1600–1930. - Zhao, Xiaotong (Lexikos, 2025)
Review of Stephen Turton. Before the Word was Queer: Sexuality and the English Dictionary, 1600–1930.